Analysis of the Relevance Curriculum With the World of Work Needs and the World of Business - Sahade Sahade; Yusuf A. Ngampo (Kontigensi : Jurnal Ilmiah Manajemen, 2021)
This study aims to describe the level of relevance of the learning curriculum of the Accounting Education Study Program, Faculty of Economics, Makassar State University with the needs of the world of work as an employee working in the accounting field. The variables in this study are the learning curriculum of the Accounting Education Study Program and the needs of the world of work as an employee who works in the accounting field. The population in this study were all alumni of the Accounting Education Study Program, Faculty of Economics, Makassar State University who had worked as company employees in the accounting field for 2007, 2008, and 2009 who had worked in accounting as accounting staff 7 people, admin staff in finance 7 people. and 1 auditor. The sample in this study is also all alumni who work as company employees in the accounting field, with a minimum working period of six months, and domiciled in Makassar as many as 15 people who meet the sample criteria. Data was collected by using library research techniques, questionnaires, documentation and interviews. The hypothesis in this study is that the curriculum of the Accounting Education Study Program, Faculty of Economics, Makassar State University is relevant to the needs of the world of work and the business world as an employee of a company in the field of accounting. The results and discussion of the research, based on the results of data analysis, it was found that from 6 (six) indicators assessed, namely 1) the speed of alumni in obtaining jobs according to their expertise; 2) job profile; 3) position and workload; 4) ability to complete work; 5) benefits of courses programmed in lectures; and 6) graduate suggestions for improving graduate competencies, with the criteria for assessing the level of relevance according to Arikunto (2016: 246) A (relevant); B (fairly relevant); C (less relevant); and D (irrelevant), then the overall result of the answer choices is 15 x 17 = 255 choices. Where there are 54 total answer choices A or 21.18%, 145 total answer choices B or 56.87%, 48 total answer choices C or 18.82%, and 8 total answer choices D or 3.13% of the total answer choices . From these data, it can be concluded that the level of relevance of the Accounting Education Study Program curriculum to the needs of the world of work and the industrial world as employees at companies in the city of Makassar, based on the closed questionnaire distributed, can be stated to be quite relevant, as evidenced by the majority of respondents choosing the answer B or 56. ,87% of the total answer choices, so the hypothesis is declared "accepted".